1974
DOI: 10.1037/h0035867
|View full text |Cite
|
Sign up to set email alerts
|

Laws of visual choice reaction time.

Abstract: The published data of 59 visual choice reaction time studies were used to determine the most significant independent variables and to develop empirical functions for them. The functions were then applied in conjunction with a proposed modification of Bonders' law to isolate the relative temporal contributions to choice reaction time of four stages of information processing identified as stimulus coding, stimulus-stimulus translation, stimulus-response translation, and response selection. Of these, coding appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
145
2
2

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(167 citation statements)
references
References 58 publications
16
145
2
2
Order By: Relevance
“…The y-intercept is simply 2mt r , and setting SD equal to zero and solving for RT reveals that the x-intercept is equal to the duration of the response component, t r . As may be seen in Figure 5, the observed x-intercept of approximately300 msec is in keeping with values for simple and choice RTs to highly discriminable stimuli reported in the literature (for a review, see Teichner & Krebs, 1974) and is therefore consistent with the two-compartment assumption of our difference engine model.…”
Section: A Two-compartment Model Of Within-groups Variabilitysupporting
confidence: 68%
“…The y-intercept is simply 2mt r , and setting SD equal to zero and solving for RT reveals that the x-intercept is equal to the duration of the response component, t r . As may be seen in Figure 5, the observed x-intercept of approximately300 msec is in keeping with values for simple and choice RTs to highly discriminable stimuli reported in the literature (for a review, see Teichner & Krebs, 1974) and is therefore consistent with the two-compartment assumption of our difference engine model.…”
Section: A Two-compartment Model Of Within-groups Variabilitysupporting
confidence: 68%
“…As expected, the target, which occurs less frequently than the non-targets, is processed slowest (Teichner and Krebs, 1974). As in a previous experiment by Herrmann and Mecklinger (2000), this was also the case when the Kanizsa square was the target, which would otherwise be expected to be processed faster than a non-Kanizsa square due to its figural features (Pomerantz, 1983).…”
Section: Discussionsupporting
confidence: 57%
“…Even more strikingly, perhaps, Teichner and Krebs (1974) have reported that simple reaction times were shorter to normal than to backward letters despite the fact that the very identity of the letters was quite irrelevant to the task. Although one is forced to conclude that subjects compulsively encode information beyond the level required by the demands of the task, this result also implies that the left-right distinction is registered early in processing.…”
Section: Discussionmentioning
confidence: 99%